A TAXONOMIC KEY FOR YELLOW CAMELLIAS IN THE CENTRAL HIGHLANDS OF VIETNAM - Tran, Ninh (Trường Đại học Đà Lạt, 2023)
Eighteen yellow Camellia species are found in the Central Highlands of Vietnam. Their morphological characteristics are described and illustrated. Based on the morphological characteristics of the leaves, flowers, and fruit, a dichotomous key has been constructed.